Polychlorinated biphenyl diffusion through HDPE geomembrane. Issue 6 (15th April 2016) - Rowe, R. K.; Jones, D. D.; Rutter, A.
Abstract : Experiments conducted to evaluate the partitioning coefficient from aqueous solution into and out of high-density polyethylene geomembrane, as well as the diffusion coefficient through the geomembrane are reported. The best estimate partitioning coefficient ( S gf ) is about 150 000 with an upper-bound estimate of 325 000. The best estimate diffusion coefficient ( D g ) is 1.0 × 10 −14  m 2 /s, with lower and upper bounds of 0.5 × 10 −14 and 5 × 10 −14, respectively. Using the diffusive properties obtained from the above experiments, the potential impacts on an aquifer of the migration of polychlorinated biphenyls and chloride are compared for a composite liner in a hypothetical municipal solid waste landfill. It is shown that, with good construction quality assurance to limit the number of holes and length of covered wrinkles to acceptably low values, a modern composite liner limited the impact of polychlorinated biphenyls on the aquifer concentration to well below regulatory limits.